Waiting for signalling quality - Hikmet Gunay (Osaka University, Institute of Social and Economic Research (ISER), 2013)
When a durable good of uncertain quality is introduced to the market, some consumers strategically delay their buying to the next period with the hope of learning the unknown quality. We analyze the monopolist's pricing and waiting strategies when consumers have strategic delay incentives. We show when the monopolist offers introductory low prices in pooling equilibria. We also find two types of separating equilibria: one where high type signals its quality by choosing a different price than the low type in the first period, and another where the high-type monopolist announces the product in the first period and waits to sell only in the second period. Waiting creates a credible cost for signalling; hence, the monopolist uses it as a signalling device.
Keywords: C73; D42; D83; L12; 330; Strategic delay; Introductory prices; Penetration pricing; Cream-skimming; Monopoly pricing; Coasian dynamics; Produktentwicklung; Konsumentenverhalten; Signalling; Coase-Theorem; Monopol; Theorie